STATUS PIRATÓW W ŚWIETLE RZYMSKIEGO PRAWA PUBLICZNEGO I IUS GENTIUM - Tarwacka, Anna (Zeszyty Prawnicze, 2017)
The Status of the Pirates in the Light of the Roman Public Law and ius gentium Summary The Roman law of war was extremely strict and formal. To declare a war (bellum iustum) it was necessary to perform a certain ceremony traditionally conducted by the fetiales. According to Cicero, a campaign against the pirates was not considered bellum iustum due to the fact that they could not be called hostes legitimi. The reason for such opinion was that their community could not be defined as a state. Cicero claims that the pirates were enemies of all mankind (communis hostis omnium). The jurists of the classical period (Pomponius, Ulpianus) shared this view calling those, who did not fulfill the conditions of gaining the status of hostes legitimi, simply bandits - latrunculi. Accordingly, a general who won a campaign against the pirates could not celebrate a triumph, which was a ceremony reserved for more splendid victories. Roman classical law considered people captured by the pirates free. They did not lose any of their rights and did not need to use ius postliminii to regain their status.